Hubungan Gaya Belajar Visual,Auditorial,Kinestetik Dengan Hasil Belajar Mahasiswa Tingkat 1 Jurusan Kebidanan Prodi Div Kebidanan Di Poltekkes Kemenkes Palu - olkamin; mutmainnah (Jurnal Bidan Cendrawasih Palu, 2019)
The DIV student learning style and the level of I applied by the students of the Dharma study with memorization before the test was not able to keep in mind the lessons given prior to memorizing. Learning styles are shared by visual learning, auditory and kinetic learning styles. Through developing the potential of sending students to hone learning learning, they have the potential for learning in achieving beneficial learning outcomes, especially for finding a midwife. Students need to get a learning style to be effective in multiplying learning to obtain good learning outcomes. The purpose of this study is to know the relationship between learning outcomes and student learning outcomes in the Department of Midwifery of the Department of Midwifery Study Program DIV Midwifery at the Polytechnic Ministry of Health, Medan. This research uses analytic survey method by using cross sectional, total population sampling technique with 94 respondents, taking data using primary data by filling out questionnaires, data analysis is done univariately and bivariately using chi square statistical test with 95% confidence level (95% Î± = 0.05). The results of the study were not able to relate the visual, auditory, and kinetic learning styles to the learning outcomes. Statistical test results showed a learning style study with a semester achievement index obtained p value of 0.88 (p value> 0.05) The conclusion of this research is the price of student learning and the results of learning 2.75-3.50, there is no relationship between visual learning style, auditory, kinesthetic learning with student learning outcomes in Midwifery Study Program Study Program DIV Midwife I in Palu Health Ministry. Suggestions for further researchers to study the learning style of other factors that affect student learning outcomes.